Adherence factors to multi-micronutrient supplementation in children under 36 months of Monsefú, 2020 - Uceda Vasquez, Noelia Melina (2021)
Objective: Determines the degree of adherence factors to multi-micronutrient supplementation in children under 36 months of Monsefú, 2020.  Method: The population and sample was made up of 100 mothers of children under 36 months who went at Monsefú’s Health Center. The sampling was not probabilistic for convenience and the data collection was carried out through a fact sheet and the test carried out by Espichan. The data were processed and were calculated absolute frequencies and measures of central tendency, in addition the reliability of the instrument was measured throught Cronbach’s alpha. During the research process, ethical and scientific criteria of rigour were met. Main results: That 97% of mothers obtain a degree of "regular" adherence. The dimension with the highest percentage of mothers with high adherence corresponds to the factors of the multimicronutrient supplement (35%). The highest percentage of regular adherence was obtained by the dimension of the health personnel factors (99%) and the highest percentage of low adherence, the dimension of socioeconomic factors (17%). General conclusion: The health personnel dimension had the highest percentage of mothers with regular adherence, the most relevant factor being the mothers' distrust of the information provided by health personnel, triggering a series of factors that do not contribute to the achievement of a high degree of adherence in the remaining four dimensions.